Pengaruh Ruang Terbuka Hijau Terhadap Kondisi Iklim Mikro di Kota Kendari: Studi Literatur - Khairiyah, Shofa‘ Nur Amirah (Journal of Geographical Sciences and Education, 2024)
Green Open Space is one of the solutions to the problem of discomfort and thermal control in microclimate, especially in urban areas such as Kendari city. This study aims to determine the effect of green open space on microclimate conditions in Kendari city. This type of research is qualitative research with literature study through reviewing related literature. Then, the analysis of several journals and books related to the discussion material will be described descriptively. Walikota Kendari Park has a wind speed of 0.59 m/s, a temperature of 33.58oC, and an air humidity of 49.77%Rh. The annual average of Kendari city is in the range of 6.8 m/s, 32.67oC, and 93.5%Rh. The existence of green spaces still has little impact on the microclimate of Kendari City green spaces. So, it is necessary to optimize the minimum target of green open space in Kendari city.